Emergency Fuel Distribution Strategy in Conditions of Transportation Access Disruption due to Flooding: A Case Study of the Sumatra Region - Mustika, Revika Shintha; Lestiani, Melia Eka (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Transportation disruptions caused by flooding in the Sumatra region often lead to the paralysis of fuel distribution, impacting economic stability and emergency services. This study aims to develop a resilient emergency distribution strategy by identifying critical risks and root causes of failure. The methods used are the integration of Failure Mode and Effect Analysis (FMEA) to determine risk priorities through Risk Priority Number (RPN) and Fault Tree Analysis (FTA) to track the root causes of technical and managerial failures. The results of the study show that seven risk indicators exceed the Critical Value of the average Total RPN Value of 186,89, with the highest risks being in the Fuel Distribution Infrastructure (252.93) and Main Line Vulnerability (226.38). FTA analysis confirmed that dependence on satellite connections in blank spot areas and bureaucratic obstacles were the main factors hindering distribution. As a solution, a Risk Response Plan was developed, which includes:1) Preventive Action through automatic data synchronization (Digital Ground Checking) and a Green Route MoU; 2) Mitigation through the provision of an alternative fleet (4x4 and ships) with a standby contract system; and 3) Corrective Action in the form of mobilizing heavy equipment and a rapid recovery team. This study provides a strategic framework for maintaining regional energy security even when land infrastructure is completely disrupted.